Initial Clinical Experience with the Biodegradable AbsnowTM Device for Percutaneous Closure of Atrial Septal Defect: A 3-Year Follow-Up - Yifan Li; Yumei Xie; Boning Li; Zhaofeng Xie; Junjun Shen; Shushui Wang; Zhiwei Zhang (Journal of Interventional Cardiology)
Objective. We reported the 3-year follow-up results of initial clinical experience with the AbsnowTM device, a novel biodegradable occluder for percutaneous closure of atrial septal defect (ASD). Background. The AbsnowTM device is a total biodegradable septal occluder with double-disc poly-L-lactic acid (PLLA) framework and PLLA membranes intergraded into the device to ensure its biodegradability, clinical safety, and efficacy. Methods. Five pediatric patients were enrolled from May to June 2018 in our institution and were followed up for 3 years. A clinical evaluation and transthoracic echocardiography were performed at 24 hr, 1 month, 3 months, 6 months, 12 months, and yearly after implantation. Primary endpoints were a composite clinical success, comprising of clinical closure success and safety at the 36-month follow-up evaluation. Secondary endpoints included technical success, procedure success, closure success, and safety at each of the follow-up visits. Results. The median subject age was 3.6 years (range 3.1–6.5 years). The mean ASD diameter was (13.7 ± 2.9) mm. The median device size was 20 mm (range 14 to 24 mm). Technical and procedure success was achieved in 100% (5/5) of the patients. At 2-year follow-up, 3 of the 5 patients developed new-onset residual shunts and 2 of them reached a moderate degree. At 3-year follow-up, the residual shunt size increased over time in all the 3 patients, and 1 of them had right ventricular enlargement. All of the 5 patients were free from serious adverse events during the 3-year follow-up, with no device embolization, thromboembolization, or reintervention to the target defect. Conclusion. This 3-year follow-up result of initial experience with the biodegradable AbsnowTM device has demonstrated acceptable safety with no procedural complications. Notably, the high rate of residual shunt significantly affected its efficacy. The long-term safety and efficacy of the device should be further evaluated in a large cohort of patients in future studies.